Paola Santiago and the sanctuary of shadows - Mejia, Tehlor Kay (Mejia, Tehlor Kay. Paola Santiago, 2022)
"Thirteen-year-old Paola Santiago must return to the void to rescue her best friend Dante and face her biggest foe yet: El Cucuy, the lord of nightmares"--